A Critical Study of Al-Farabi Philosophy Implementation at Education non Islamic Higher Education in Indonesia - Ahmad Asmuni (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The purpose of this study is to conduct a critical study of Alfarabi's philosophy in the implementation of education at Islamic universities in Indonesia. The research method used is a literature study using a philosophical approach. The main data sources are secondary data in the form of Alfarabi's work entitled Risalah fi al-'Aql and previous research works that reveal the philosophical thoughts of Islamic education put forward by Alfarabi. The findings reveal that the Alfarabi philosophy is implemented in the practice of education at Islamic universities in Indonesia through the scope, objectives, and benefits of education. First, the scope of education taught is about the concept of reason (intelligence). Second, the purpose of education is to prepare students through the transfer of knowledge and practical skills to obtain the perfection of life as human beings. Third, the benefits of the concept of value through morality development, teaching methods, and learning evaluation. The conclusion of the research is that Afarabi's philosophy in implementing education in higher education is very important for students and lecturers to improve self-competence. The expected implication is that Islamic Universities not only focus on information and communication technology, but also implement the values ​​of an Islamic philosophy of life in accordance with the guidelines of the Qur'an and al-Hadith.